Identification of novel variants underlying non-syndromic primary ovarian insufficiency using a targeted NGS gene panel - Veneziano, Claudia; Parrotta, Jessica; Lico, Daniela; Santamaria, Gianluca; Antonucci, Gemma; De Angelis, Maria Teresa; Zullo, Fulvio; Viglietto, Giuseppe; De Marco, Carmela; Venturella, Roberta (Frontiers in Endocrinology, 2025)
Background and objectivesPrimary ovarian insufficiency (POI) affects 1-4% of women and is associated with infertility and reduced life expectancy. Most cases are idiopathic, and a genetic alteration is often the most plausible cause. In this study, we investigated whether targeted next-generation sequencing (NGS) analysis in combination with the OvAge© method, which integrates biochemical and ecographic parameters, can reliably identify specific genetic variants underlying the occurrence of non-syndromic primary ovarian insufficiency (nsPOI).MethodsWe enrolled 100 women with nsPOI and 200 healthy controls. A targeted NGS panel covering 72 genes potentially involved in POI was developed using Ampliseq technology (ThermoFisher Scientific). Various bioinformatic tools (Polyphen, Sift, CADD, MutationTaster and the Grantham score) were used to identify potentially pathogenic variants according to ACMG guidelines, while tools such as STRVCTVRE, CADD-SV and X-CNV were used to predict pathogenicity of CNV calls.ResultsUsing this panel, we identified mutations in 60% (N=60) of the patients, of whom 23% carried likely pathogenic or pathogenic mutations, and 37% had variants of uncertain significance (VUS). Among these 60 patients, 37 had monogenetic variants and 23 had mutations in two or more genes. In total, we identified 42 genes affected in our Italian of nsPOI cohort. The most frequently mutated genes in our cohort included DNAH5, LAMC1, ADAMTS1/19, HSD17B4, HK3 and AR. Additionally, we detected CNVs in the SYCE, DUSP22 and INHBB genes. Most of the altered genes in our cohort are involved in DNA repair, meiosis and signal transduction. Gene Ontology (GO) analysis revealed that the mutated genes play a key role in oocyte differentiation, folliculogenesis and follicular maturation.DiscussionOur main conclusion is that the development of a test integrating clinical, ultrasound, biochemical (OvAge©) and genetic data could substantially enhance early identification of women at risk of POI and offer opportunities for fertility preservation, such as oocyte cryopreservation or prioritizing reproductive efforts.